Description of the nucleolar activity and karyotype in germinative cell lines of Rhodnius domesticus (Triatominae, Heteroptera) - Morielle, Alessandra [UNESP]; Oliveira, Maria Tercília Vilela de Azeredo [UNESP] (Firenze University Press, 2004)
The purpose of this work was to study the karyotype, spermatogenesis and nucleolar activity at meiosis, in the species Rhodnius domesticus (Heteroptera, Triatominae). The testicular tubules were cytologically prepared by the conventional method of cell crushing and subsequent application of cytogenetic staining techniques with lacto-acetic orcein and silver-ion impregnation. The species under study presented karyotype 2n= 20A+XY, the modal number of the subfamily Triatominae. The chromosomes presented no primary constriction and were therefore characterized as holocentric. It was observed that the sex chromosomes sometimes were located at the periphery, close to the ring formed by autosomes, at first meiotic division. At metaphases II, sex chromosomes were positioned in the center of the autosomal ring, thus evidencing a postreductional behavior. These same chromosomes showed late migration at anaphases and were clearly impregnated with silver-ions, suggesting they bore Nucleolar Organizer Regions. Dispersed nucleolar corpuscles in cytoplasm until telophase II and small dots in spermatids strongly impregnated with silver, could be seen. Thus, it may be inferred that, in triatomines, the nucleolus does not completely disappear but remains in the form of small corpuscles that have a role in cell differentiation.
Keywords: Germinative lines; Karyotype; Nucleolar Organizer Region; Nucleolar persistence; Nucleolus; Rhodnius domesticus; Heteroptera; Rhodnius; Triatominae